PENGARUH PROFITABILITAS, KEBIJAKAN HUTANG DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEPEMILIKAN MANAJERIAL DAN PENGARUHNYA TERHADAP RISIKO - KARTIKA NURINGSIH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2010)
This research model analyses managerial ownership from three determinants: profitability, debt policy and institutional ownership. Then, the research model also analyses the effect of managerial owner-ship on risk. Based on agency theory, the developing of the model is used to reduce the potential conflict in company. Samples were taken from 319 companies which listed at Indonesia Capital Market Directory period 2001 until 2004. The results of research show that debt policy and institutional ownership have negative effect to managerial owner-ship. While, profitability has not effect to managerial ownership. Managerial ownership has negative effect to risk. From the results can be concluded that the effect of profitability on managerial ownership can not be used to control agency conflict, meanwhile another hypo-thesis can be received to reduce agency conflicts